2022
DOI: 10.3390/cancers14112658
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Human Pan-Cancer Analysis of Cyclin-Dependent Kinase 1 (CDK1)

Abstract: Cyclin-dependent kinase 1 (CDK1) is essential for cell division by regulating the G2/M phase and mitosis. CDK1 overexpression can also promote the development and progression of a variety of cancers. However, the significance of CDK1 in the formation, progression, and prognosis of human pan-cancer remains unclear. In the present study, we used The Cancer Genome Atlas database, Clinical Proteomic Tumor Analysis Consortium, Human Protein Atlas, Genotype-Tissue Expression, and other well-established databases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…During the G2/M phase and mitosis, CDK1 is essential to regulate cell division. In a variety of cancers, overexpression of CDK1 can also promote their development and progression [42]. It has already been con rmed that CDK1 is associated with cellular mobility and proliferation, and it is downregulated with THRIL overexpression [43].…”
Section: Discussionmentioning
confidence: 99%
“…During the G2/M phase and mitosis, CDK1 is essential to regulate cell division. In a variety of cancers, overexpression of CDK1 can also promote their development and progression [42]. It has already been con rmed that CDK1 is associated with cellular mobility and proliferation, and it is downregulated with THRIL overexpression [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cell cycle-independent function of CDK1 in enhancing overall protein synthesis has been uncovered [51]. An integrative human pan-cancer analysis showed that dysregulation of CDK1 was identified in more than 20 human tumors and was significantly correlated with the development, progression, and microenvironment of tumor cells [52]. Lowdose radiation exposure alters the expression of CDK1, which is associated with post-Chernobyl PTC development [53].…”
Section: Discussionmentioning
confidence: 99%
“…Its dysregulation is common in many tumors of diverse origins, leading to chromosomal instability via replication stress and enhanced proliferation of cells. A recent pan-cancer integrative analysis based on TCGA and GTEx databases performed by Liu et al (2022) showed that CDK1 expression levels are increased in many tumor types when compared to normal tissues and are generally associated with poor clinical prognosis [ 336 ]. For example, CDK1 expression is positively and highly associated with advanced cancer stages in lung and endometrial cancer [ 337 , 338 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%